ANXIETY AND DEFENCE MECHANISM REFLECTED IN THE POETRY ANTHOLOGY BY ADI K - salsabila nur fadhilah sayuti (Universitas Negeri Medan, 2026)
This study investigates how anxiety and defense mechanisms are reflected in Being Unhappy Is a Choice, a poetry anthology by Adi K, using Freud’s psychoanalytic theory as the analytical framework. The research applies a qualitative descriptive method to identify and interpret psychological aspects represented in selected poems. The analysis reveals that the anthology portrays three types of anxiety: reality anxiety, neurotic anxiety, and moral anxiety. These anxieties are expressed through themes of fear, inner conflict, guilt, and self-doubt. In response to these anxieties, the poems demonstrate the use of defense mechanisms such as rationalization, sublimation, reaction formation, and introjection. The findings suggest that Adi K’s poetry not only conveys individual struggles but also illustrates how hidden fears and emotional pain can be transformed into creative expression. By combining literary and psychological perspectives, this research highlights how poetry serves as both an outlet for unconscious conflict and a medium for readers to reflect on their own emotional experiences. The study contributes to the field of literary psychology by expanding psychoanalytic analysis into contemporary Indonesian poetry, offering new insights into the intersection of literature, mental health, and human resilience. Keywords: Adi K, Anxiety, Defense Mechanisms, Indonesian Literature, Psychoanalysis